The Development of Non-Colinear Fault Systems: What Can We Learn From 3D Seismic Reflection Data? - Reeve,MT; Bell,RE; Duffy,OB; Jackson,CA-L; Sansom,E (Journal of Structural Geology, 2014)
Many rift zones exhibit a range of fault orientations, rather than simple colinear faults that strike orthogonal to the least principal stress. The formation of non-colinear fault sets has implications in assessing rift zone kinematics, as well as determining the palaeo-stress state in extensional basins. Using high-resolution borehole-constrained 3D seismic reflection data we deduce the likely mechanisms responsible for the formation of a population of non-colinear faults in the Måløy Slope area of the northern North Sea. Three basement-displacing fault populations exist on the Måløy Slope; (i) large (>1 km throw), N-S-striking faults, and smaller (<250 m throw) (ii) N-S- and (iii) NE-SW-striking faults, all of which initiated in the Middle Jurassic. Coeval growth of these fault populations, and the apparent correlation between the NE-SW faults and a NE-SW-trending gravity and magnetic anomaly high suggests that variation in basement properties may have represented a NE-SW trending zone of weakness which was subsequently exploited during Jurassic extension. The results of our study have critical implications for understanding the larger-scale kinematic evolution of the North Sea rift, arguing that major rotations in the extension direction are not required to generate multiple fault sets locally or across the rift.